Pbl and Cdio for Engineering Education: A Polynesian Canoes Case Study - Alfaro-Marchant, M (Institute of Electrical and Electronics Engineers Inc., 2018)
A design of nautical project using project-based learning was developed by collaborative partners and implement in two different Universities in Chile. The experience uses the concurrent engineering supported by computing platform and design techniques: Computational Fluid Dynamics (CFD), Computer Aided Manufacturing (CAM), Finite Element Method (FEM) and Computer Aided Design (CAD) as tools for enhancing the innovative capacity of students. Interdisciplinary teams are grouped by capacities and technical interests, they worked in the developing stages of the project of naval team for an international competition. The design and construction areas are approached all the technical components for a naval team; the 3d digital concept, the ergonometric studies, the computational simulations, the hydrodynamics, the resistance analysis of materials, the processes engineer, the 3D prototype, and the assisted manufacturing on computer. The research presents the obtained results by the two teams, the PBL comparison with lecture course, outcomes, and challenges. © 2018 IEEE.